Modeling Battery Energy Storage System operating in DC microgrid with DAB converter - Santos, Rafael Dos [UNESP]; Goncalves, Flavio A. S. [UNESP]; Olimpio Filho, Jose A. [UNESP]; Marafao, Fernando P. [UNESP]; Gil, Eric (Institute of Electrical and Electronics Engineers (IEEE), 2019)
This paper presents a computational model for studying the energy flow at the integration of a battery bank (BB) to a DC microgrid, through the use of the Dual Active Bridge (DAB) converter. The one time constant model was adopted for the battery, with its parameters obtained through exponential regression by the Least Squares method, through its hysteresis curve between terminal voltage and load level percentage. The curve was synthesized by data collected from a LiFeYPO4 reference battery. The DAB converter was controlled by the Phase-Shift modulation technique. The converter power management occurs through a state machine, which defines the conditions of energy flow between the microgrid and the energy storage system. This paper has educational aims for the study of energy flow at the integration of BB into DC microgrids.
Keywords: Battery Banks; DAB; DC Microgrid; State Machines